Editorial: low population mortality from COVID-19 in countries south of latitude 35 degrees North supports vitamin D as a factor determining severity. - Kenny, Rose; Laird, Eamon (My University, 2020)
The excellent review by Al-Ani et al reflects a consensus approach to management of inflammatory bowel disease during the SARS-CoV-2 pandemic that has been established remarkably rapidly by very effective international collaboration. Much of the focus has appropriately been on the potential impact of immuno-modulating therapies. We would also like to highlight the potential importance of nutrition and particularly vitamin D as raised by Panarese and Shahini.
PUBLISHED
Keywords: inflammatory bowel disease; SARS-CoV-2; consensus approach; inflammatory bowel disease; SARS-CoV-2; consensus approach; Ageing